Recognition of species groups of Naupactus Dejean (Coleoptera: Curculionidae) from Argentina and neighboring countries - Río, María Guadalupe del (2019)
Naupactus Dejean is the most diverse genus of the tribe Naupactini (Curculionidae: Entiminae), with more than 200 species occurring in South America, of which about 40 range in Argentina and neighboring countries. The Argentinean species treated herein were classified into nine groups having different biogeographic patterns: (1) the groups of Naupactus xanthographus, N. delicatulus and N. auricinctus mainly occur in northeastern Argentina (Misiones province) and reach the highest species diversity in the Atlantic and Parana forests of Brazil; (2) the groups of N. hirtellus, N. cinereidorsum, N. rivulosus and N. tarsalis show the highest species diversity in the Chacoan biogeographic province and also occur in the Yungas, Espinal, Monte, Parana forest (Argentina) and Cerrado (Brazil); (3) the groups of N. leucoloma and N. purpureoviolaceus have the highest species diversity in the Pampean biogeographic province, being also present in adjoining areas, mainly Chaco, Espinal, Monte and Parana forest. We provide descriptions, a dichotomous key, habitus photographs and line drawings of genitalia for the identification of the nine species groups, and a list of the Argentinean species from each group, together with their abbreviated synonymies, updated geographic distributions (including six new country records and several state/province records) and host plant associations. We discuss the characters that allow the separation of the species groups in a geographic distribution context, and provide information on species reassigned to genera other than Naupactus; among these, we transferred N. cephalotes (Hustache) to the tribe Tanymecini, genus Eurymetopellus, establishing the new combination Eurymetopellus cephalotes.